Penerapan Green Office pada Kementrian Kesehatan Republik Indonesia - Fitriani, Dian; Astuti, Sri (Utilitas, 2016)
This qualitative research intended to acknowledge the application of âgreen office conceptâ at Housekeeping Department of Ministry of Health of Indonesia. The researcher captured the data from the research field factually. Data gathered from the responsible staffs purposively, data collection methods used were moderate participant observation, indepth interview, and document analysis. The data validated by technique triangulation and resource triangulation.The qualitative research resultshowed that (1) the staffs have moderate commitment for âgreen officeâbehavior. As showed by the paper saving, electricity saving, water saving, waste management, greening, cleanliness, and roomâs air conditioning; (2) Eco â friendly office technology applied by using information technology system as electronic mail, electronic filling system and web based communication group.(3) The office physical building design suitable for naturally lighting design with lightsâ placement grouping system, and also considers building green coefficient.(4) Vehicle cleaning and watering trees with condensed water were prohibited.(5) Office materials selected to minimize the use of papers and tissues. (6) Air conservation system applied by using centralized Air Conditioning System with average degree 24 â 25 celcius. (7) Airhumidity about 55% with no smoking rule. (8) Electric saving lights used by grouping system and also there was motion sensor lights at the bathroom; (9) flush the plant with Air Conditioning condensed water.